UPAYA PENGUATAN NILAI KEARIFAN LOKAL DESA WISATA NGLANGGERAN GUNUNG KIDUL SECARA BERKELANJUTAN - Novi Irawati; Heni Dwi Lestari; Wahyu Puja Kesuma (Kepariwisataan: Jurnal Ilmiah, 2022)
The concept of sustainable tourism is one of the best concepts developed by the government and tourism stakeholders to be applied in every tourist destination. The Covid-19 pandemic has forced tourism activists to work together to revive the economy in the tourism sector. Through the development of the concept of Sustainable Tourism, the manager of the Nglanggeran tourism village has made several efforts to strengthen the value of local wisdom from the beginning of its establishment, however, with the many competitors and the rapid development of tourism, the manager of the Nglanggeran tourist village has always innovated and strengthened local wisdom. With a case study analysis approach, it is hoped that it will describe some of the efforts made by the management regarding the strategy of strengthening the value of sustainable local wisdom from various aspects, namely environmental aspects, economic aspects, social aspects and cultural aspects.Keywords: Sustainable Tourism, Local Wisdom, Nglanggeran Tourism Village